Ekaristi Sebagai Pusat Liturgi: Analisis Teologis Berdasarkan Sacrosantum Consilium Artikel 10 - Pribadi Barus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This research aims to analyze theologically the position of the Eucharist as the center of the liturgy as affirmed in Sacrosanctum Concilium article 10. Through a qualitative approach with the method of analyzing Church documents, this study explores the theological meaning of the Eucharist as the source (fons) and peak (culmen) of the Church's life. The results of the study show that the Eucharist has a central role in the liturgical life and faith of the faithful, because it contains all the works of Christ's salvation that continue to be presented in the life of the Church. The Eucharist is not just a ritual celebration, but a real encounter with Christ who sanctifies, unites, and sends the Church to mission in the world. Thus, all the Church's activities originate in and culminate in the Eucharist, making it the center and pinnacle of Christian life. This research confirms that a theological understanding of the Eucharist not only enriches the reflection of the faith, but also provides practical direction for the liturgy and pastoral of the Church. The Eucharist is the foundation that affirms the identity of the Church as a living community of Christ and sent to bring God's love in the midst of the world. From this perspective, the Eucharist is truly the essence of the life of the Church that animates the entire practice of faith of the faithful.